Evaluation of some Virulence Factors, Hemagglutination and Agglutination of Antigens of Acinetobacter baumannii Isolated From Clinical Samples - Fatima Rammadan Abdul (Journal of Global Pharma Technology, 2018)
A total of 50 clinical samples, isolated from various sources include blood septicemia, urine (UTI), wound and burn swabs and swabs of ear (otitis media). The isolates were identified according to the microscopical , morphological ,cultural, and biochemical tests, in addition to using VITEK-2 compact system. Results showed that (12) isolates were characterized as A. baumannii. Frequency of positive A. baumannii clinical isolates was higher in blood (50%), followed urine (25%). The sensitivity of isolates to eight antibiotics, the result showed highly level of resistance for most antibiotics and multi-resistance antibiotics. It was found that all (100%) of bacteria isolates were resistant to Ampicillin and Cefazolin, while Imipenem and Tobramycin were the most effective antibiotics. The isolates showed the ability of biofilm production by Congo red agar method (CRA), 7 (58.3%) isolates positive biofilm production, while 5(41.7%) isolates are non-biofilm production. Consequences of phenotype were demonstrated 4 (33.3% %) of the detaches were protease production, while (8) isolates (%66.7) were not producers of this enzyme, while Sera proteins of patients’ infected by A. baumannii showed reactivity with A. baumannii antigens (whole cells ) as :two A. baumannii antigens agglutinated in titer 1:64 of patients sera ( antibodies ) while 6, 3 , 2 ,5 of A. baumannii antigens agglutinated in the patients sera in titer (1: 8 ,1:16,1:128,1:256) respectively. Thee hemagglutinin of A. baumannii may be a virulence factor in the pathogenesis of infection; However, results founded a good correlation between ability of biofilm formed and the hemagglutination. Keywords: Acinetobacter baumannii, Virulence factors, Biofilm, Hemagglutination.